Examining and comparing the relation between representational competence and conceptual knowledge across four samples - Edelsbrunner, Peter Adriaan; Hofer, Sarah Isabelle (Frontiers in Education, 2024)
IntroductionWhereas it is commonly assumed that in learning science, representational competence is a critical prerequisite for the acquisition of conceptual knowledge, comprehensive psychometric investigations of this assumption are rare. We undertake a step in this direction by re-analyzing the data from a recent study that found a substantial correlation between the two constructs in undergraduates in the context of field representations and electromagnetism.MethodsIn this pre-registered contribution, we re-analyzed the data (N = 515 undergraduate students; Mage = 21.81, SDage = 4.04) to examine whether the relation between representational competence and conceptual knowledge, both measured with psychometrically validated test instruments, is similar or varies between four samples from two countries. To this end, we employed correlational analysis and scatter plots. Employing these methods, we examined whether a positive relation between representational competence and conceptual knowledge can be found and is of similar magnitude in all samples. We also employed multiple-group latent profile analysis to examine how the more detailed association between the two constructs varies or is similar across samples.ResultsWe found that the relation between the two constructs was positive in all four samples, but was stronger in the samples consisting primarily of engineering and physics students than in environmental sciences and teacher education-students. All latent profiles indicated that high representational competence is a prerequisite for high conceptual knowledge, but not vice versa. We found little relation to learners’ gender and topic-specific learning opportunities in high school.DiscussionThese results indicate that the qualitative findings of a positive relation between representational competence and conceptual knowledge, with no evidence of learners that achieve high conceptual knowledge with low representational competence, generalize across different populations. We derive hypotheses for further moderating factors that can be examined in future research.